DISTRIBUTION OF MICROELEMENTS NI, CO, MN and Zn IN SOME TISSUES RATS - Nurimov Pakhlavon Bakhtiorovich; Umirov Abdulla Sulaimonovich (Scholar Express Journals, 2023)
Microelements Ni, Co, Mn and Zn in some tissues of rats in this work I study distribution. To do this, the internal organs of rats are the kidneys, muscles, lungs and liver. there is a change in its composition. Determine the amount of trace elements in the body of mammals The experiment was carried out on rats bred for experiments in two districts of the city of Samarkand. Samarkand, Liver, lungs, muscles and kidney organs of two rats from each Taylak region. experiment was carried out on tissues. Experience of scientific expertise of Samarkand State University carried out in the laboratory. Trace elements using the biochemical apparatus "Sobus111" this experiment has been defined. According to the results, the amount of Zn in the body is higher than other trace elements. This. Zinc is mainly found in the muscles, less in the liver than in the muscles, less in the kidneys than in the liver. it is less in the lungs than in the kidneys. The amount of Mn in the body is small compared to Zn. He's with a cookie almost the same amount in the kidneys. The amount of Mn in the lungs is four compared to the liver and kidneys. one and a half times less, and in the muscles seventeen times less. Sum of Ni with Co there are very few of them in the tissues of the body, because these microelements are toxic substances Considered The examination showed that trace elements Ni, Co, Mn and Zn are present in the tissues. lack of metabolism slows down, immune - supplement cells and functional organs decreased activity negatively affects the development of bone tissue. [5,7,9,12]
Keywords: Cobalt; Nickel; Manganese; Zinc